Knights Across the Atlantic Intimidation, Coercion, and Communities During the Irish Revolution - Parfitt, Steven (Studies in Labour History, 2017)
Knights Across the Atlantic tells for the first time the full story of the Knights of Labor in Britain and Ireland, where they operated between 1883 and the end of the century. British and Irish Knights drew on the resources of their vast Order to establish a chain of branches through England, Wales, Scotland and Ireland that numbered more than 10,000 members at its peak. British and Irish Knights left a profound imprint on subsequent British labour history. They helped inspire the British "New Unionists" of the 1890s and influenced the movement for working-class politics, independent of Liberals and Conservatives alike, that soon led to the British Labour Party. Knights Across the Atlantic provides new insights into relationships between class and gender, and places the Knights of Labor squarely at the heart of British and Irish as well as American history at the end of the nineteenth century.